2014
DOI: 10.1111/cas.12332
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tregs by anti‐glucocorticoid induced TNF receptor antibody enhances the antitumor immunity of interferon‐α gene therapy for pancreatic cancer

Abstract: We have reported that interferon (IFN)-α can attack cancer cells by multiple antitumor mechanisms including the induction of direct cancer cell death and the enhancement of an immune response in several pancreatic cancer models. However, an immunotolerant microenvironment in the tumors is often responsible for the failure of the cancer immunotherapy. Here we examined whether the suppression of regulatory T cells (Tregs) within tumors can enhance an antitumor immunity induced by an intratumoral IFN-α gene trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…[139,140] Recently, antiglucocorticoid-induced TNF receptor monoclonal antibody has been introduced to suppress Tregs. Aida et al [47] showed this monoclonal antibody-induced suppression of Tregs infiltration in PC with down regulation of CCR5 and led to enhancement antitumor immunity of IFN-α gene therapy.…”
Section: Adaptive Immune Cells In Pcmentioning
confidence: 99%
“…[139,140] Recently, antiglucocorticoid-induced TNF receptor monoclonal antibody has been introduced to suppress Tregs. Aida et al [47] showed this monoclonal antibody-induced suppression of Tregs infiltration in PC with down regulation of CCR5 and led to enhancement antitumor immunity of IFN-α gene therapy.…”
Section: Adaptive Immune Cells In Pcmentioning
confidence: 99%
“…Importantly, the success of therapy was seen in several tumor models, independently of tumor cell line sensitivity to NDV-mediated lysis, highlighting the importance of the virus-induced antitumor immunity rather than direct oncolysis in the observed therapeutic efficacy . A similar study using systemic agonistic anti-GITR antibody together with intratumoral administration of adenovirus expressing IFNα also resulted in synergistic inhibition of the virus-injected and distant tumors (Aida et al, 2014). Taken together, these studies thus provide a strong rationale for further evaluation of oncolytic viruses as potentiators of immunotherapy with agents targeting immune costimulatory or coinhibitory receptors.…”
Section: Oncolytic Virusesmentioning
confidence: 71%
“…Kavanagh et al observed that CTLA-4 blockade expanded Treg at low doses, but expanded effector T cells only at high doses [116]. Some studies have reported that anti-CTLA-4 or anti-GITR made effector T cells resistant to the inhibitory effect of Treg [44,117,118]. …”
Section: Mechanisms Mediating the Efficacy Of Cancer Vaccines Combmentioning
confidence: 99%